Sociological Factors of Juvenile Delinquency Makassar City, Indonesia - Syarifuddin, Nurdiyanah; Sari, Widya; Bujawati, Emmi; Susilawaty, Andi; Azriful, Azriful (Diversity: Disease Preventive of Research Integrity, 2021)
The factors that influence delinquency in adolescents are sociological factors, psychological factors, and biological factors. Sociological factors include family background, the community where adolescents are, and the school environment. This study used a qualitative method with a case study design. The number of informants was 10 people consisting of delinquency teenagers, parents of delinquency teenagers, women, and child protection investigators, and clinical psychologists at the integrated service post for women and children protection. Data collection was carried out through in-depth interviews. Data analysis was performed by source triangulation. The results showed that economic difficulties made parents have to work more. Teens have a playgroup that influences them. Problems that arise from the school environment make children not want to go back to school. This study recommends the importance of the role of parents, government officials, and schools in giving attention and guidance to adolescents in order not to act wrong, both moral guidance and religious guidance.